EFEKTIVITAS PROGRAM REHABILITASI HUTAN DAN LAHAN AGROFORESTRI DI KECAMATAN BRINGIN KABUPATEN SEMARANG - Najwa Hilalia, Nela; Warsono, Hardi; Sunu Astuti, Retno (Journal of Public Policy and Management Review, 2024)
This study is based on the phenomenon of inadequate management of vacant land in Bringin District, Semarang Regency. The objective of this research is to assess the effectiveness of the forest and agroforestry land rehabilitation program in Bringin District, Semarang Regency, and to analyze the supporting and inhibiting factors affecting its effectiveness. The study employs the policy dimensions of effectiveness theory and utilizes a descriptive quantitative analysis for data processing. Data collection was carried out through the distribution of questionnaires using purposive sampling techniques to 73 respondents. The research results are evaluated using six indicators: policy accuracy, target accuracy, process accuracy, communication, policy content, and resources. Based on two indicators, namely policy accuracy and process accuracy, the program has not yet been fully effective. In terms of policy accuracy, the issue lies in the fact that local communities lack a stable market for selling their harvests. Meanwhile, the process accuracy indicator reveals that the road access for farmers and laborers remains difficult, and the available shelters are inadequate. These findings indicate that the implementation of the forest and agroforestry land rehabilitation program in Bringin District, Semarang Regency, has yet to be effective. The researcher recommends that the Watershed and Protected Forest Management Agency (BPDASHL) consider partnering with private entities, particularly those involved in the agricultural and forestry sectors. Additionally, it is suggested to improve road access and the shelters in the planting areas to facilitate mobility and the storage of harvests and farming tools. BPDASHL could also collaborate with KTH Mandiri Jaya I to build larger shelters that meet the needs of both farmers and laborers.